مظاهر الغلو في توظيف قاعدة سد الذرائع : قضايا المرأة المعاصرة ‏أنموذجا - باشوش، راضية (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study proposes an exposition to the principle, of the Islamic Jurisprudence “Saddu al-Dharaʼiʻ” (Blocking the Means) in terms of its implementations on contemporary issues with regard to women. This study is a critical examination of selected issues addressed in this dissertation. The aforementioned examination has been made by highlighting the manifestations of extremism through its applications and impact of the Islamic characteristic of Moderation (Al-Wasatiyyah) according to the requirements of the times. Likewise, it addresses the issue of women working in the media, cultural fields as well as politics. The implementation of this principle has been discussed in these fields by presenting the verdicts and inspecting the fatwas of each area with special reference to the aspect of immoderation. The methodology applied in the research is mainly inductive, analytical, and critical. Texts from Shariah and jurisprudential views by early and contemporary scholars in this regard have are been collected and analyzed. Furthermore, a comparison is made between the opinions and views of scholars about women's issues with critical analysis in its implementation. The study concludes that the fatwas on the principle of “Saddu al-Dharaʼiʻ” are based on exaggeration and against the principles of its implementation. The study also finds that the above principle has been confused with consignment and caution. There is also no an established regulation through which the “Saddu al-Dharaʼiʻ” (Blocking the Means) principle can be achieved in any way. The researcher concludes the study by providing a detailed collection of results, as well as a series of recommendations.